Purchase by the central government of immovable properties in certain cases of transfer in India: one of the measures to mobilize revenue to fight the global economic crisis - Ansari, Abdul Haseeb (Lexis-Nexis Malaysia Sdn Bhd, 2009)
In order to alleviate the scourge of the present global economic downturn and minimise its adverse effects, states at international level, individually and collectively, are making efforts according to suitability of their economies. Among all suggested efforts, having efficient anti-evasion and anti-avoidance provisions in taxing statutes, plugging the loopholes in them, and strictly dealing with evaders and avoiders are central. It is needless to say that alleviation of evasion and avoidance will result in more revenue generation. It will also trim down the generation and utilisation of black money. The paper discusses some of the efforts made by the United States of America, the United Kingdom and the OECD, which can be considered by developing and least developed countries too. But before a measure is adopted, an economic study should essentially be made by them. Black money is generally utilised in illegal transaction(s) which, in turn, weakens the economy. If there are opportunities to utilise black money, people are encouraged to practice tax-evasion and tax-avoidance. There is a universal practice that black money is utilised in buying and constructing real estates. India took a drastic measure by introducing pre-emptive purchase in such cases and this proved to be successful for a number of years. Unfortunately, this law has been suspended. The present economic crisis warrants for re-enforcing the law, especially in developing countries, including Malaysia. But before resorting to such a measure, a thorough economic study should be made. The paper discusses various suggestions made towards fighting the global economic downturn through taxing statutes and the law of pre-emptive purchase.